A robotic vehicle with Internet of Things (IoT) capabilities to verify the compliance of Law 7600 in Costa Rica - Carrasquilla-Batista, Arys (2019)
Governmental entities worldwide are working to- wards equal opportunities environments, this principle recognizes the importance of the different needs that individuals have and of how these needs must serve as the basis for social planning, to ensure that resources are being used in ways that guarantee persons equal opportunities of access an participation in identical circumstances. In May 1996, the Legislative Assembly of Costa Rica approved the equal opportunities law for persons with disabilities, known as Law 7600. In this law there are mandatory technical specifications, issued by the corresponding public and private entities, that have to be fulfill in new building or changes in existing buildings, parks sidewalks, gardens, restrooms and other public spaces. The proposed system consists of electronic circuitry built with commercial-off-the-shelf components (COTS), affordable sensors, mobile communication, actuators and soft- ware running in the Internet. In the first iteration of the project a local computer was used to control a robotic vehicle and to process all data, in this paper an embedded system with Internet of Things (IoT) capabilities is to be implemented.